Silat Instructor Role in Student Character Development - Qoyum Firmansyah; Jauhara Rouhullah (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2024)
Silat instructors play a significant role in shaping patience and discipline in their students. This research aims to discover how the coach shapes the character of their students, the obstacles encountered, and the results of this education. The method used is qualitative. Data collection was done through observation, interviews, and documentation. The data obtained was then analyzed using the interactive analysis model, where the data is reduced to only the important aspects, and then the data is presented alongside the data collection process. Thus, after the data is collected, the three components of analysis (data reduction, data review, and conclusion drawing) interact. The results show a relationship between the instructor and the students regarding the formation character of patience and discipline. In conclusion, the combination of physical training and spiritual guidance, along with rewards for achievements and punishments for violations, trains students to be patient in facing various problems they encounter and to be disciplined with time during and outside silat practice sessions.